N-[(2-Chloro-6-methylquinolin-3-yl)methyl]aniline - Sushma Drabu; Suresh Kumar; Sandhya Bawa (Molbank, 2009)
Quinolinyl amines are important organic compounds which possess a variety of pharmacological activities such as antimalarial, antifungal, hypotensive and antidepressant activity.